Combined heat and power generation with lime production for direct air capture - Hanak, Dawid P.; Manovic, Vasilije (Elsevier, 2018)
Carbon capture and storage (CCS) has been shown to be the least cost-intensive option for decarbonisation of the power, heat, and industrial sectors. Importantly, negative-emission technologies, including direct air capture (DAC), may still be required after near-complete decarbonisation of the stationary emission sources. This study evaluates the feasibility of a novel polygeneration process for combined heat and power using a solid-oxide fuel cell, and lime production for DAC (CHP-DAC) that could contribute towards decarbonisation of the power, heat, and industrial sectors. Evaluation of the thermodynamic performance indicated that such process can achieve the total efficiency and effective electric efficiency of 65%LHV and 60%LHV, respectively, while removing CO2 from the air at a rate of 88.6 gCO2/kWchh. With the total expenditure spread over a number of revenue streams, the product prices required for the CHP-DAC process to break even were found to be competitive compared to figures for the existing standalone technologies, even if there was no revenue from CO2 capture from the air. Moreover, the considered process was shown to be economically feasible, even under uncertainty. Hence, it can be considered as the carbon–neutral polygeneration process for sustainable and affordable production of heat, power, and lime that is negative-emission ready.
Keywords: Lime production; Polygeneration; Negative emissions; Solid-oxide fuel cell; Feasibility study; Techno-economic analysis